Utilizing terror: On the adoption and refinement of skull cups in Tibetan Buddhism. - Fuentes, Ayesha. (2017)
Abstract: This thesis examines the changing role of the kapala, or skull cup, in the visual and material culture of Tantra. The transformation of the skull cup is related to the historical and religious conditions of its various ritual settings and applications in the region of northern India and Tibet. These cups are seen in depictions of terrifying or wrathful Tibetan Buddhist deities and associated with the Tantric/esoteric practices of their devotees. My paper explores the transformation of the skull cup from an object employed for its inherent quality of pollution in a marginal setting of the early centuries CE to its doctrinal and institutional value in Tibetan Buddhism of recent centuries. Integrating art historical and religious scholarship, I explore the history of skull cups and their refinement as well as their iconological resonances in Tibetan religious paintings and the arts of esoteric Buddhism.; Thesis (M.A.)--Tufts University, 2011.; Submitted to the Dept. of Art and Art History.; Advisor: Ikumi Kaminishi.; Committee: Joseph Walser, and Peter Probst.; Keywords: Art History, and Religion.